2005
DOI: 10.1007/s11095-005-5647-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Drug Particle Surface Energetics and Young’s Modulus by Atomic Force Microscopy and Inverse Gas Chromatography

Abstract: The range of determined surface energies between the AFM measurement on graphite, mica, and the drug is proposed to reflect the different chemistries displayed by the drug at the single particle level. The maximum values of these ranges can be related to the sites most likely to be involved in adhesion. AFM and IGC yield surface energy estimates in approximate agreement, but clearly are interrogating surfaces in different fashions. This raises questions as to the nature of the measurement being made by these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 55 publications
1
32
1
Order By: Relevance
“…Knowledge of surface energetics of excipients can therefore be of similar importance to that of the APIs in the formulation design of multi-component systems and the prediction of processing performance such as binder-drug adhesion, powder flow, compaction and granulation performances (2)(3)(4)(5). Common methods of characterizing the surface energetics of particulate pharmaceuticals rely on indirect approaches involving the use of characterized or known vapours, liquids or solids as probes as in inverse gas chromatography (IGC) (6), sessile drop contact angle (7) and atomic force microscopy (AFM) (8) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of surface energetics of excipients can therefore be of similar importance to that of the APIs in the formulation design of multi-component systems and the prediction of processing performance such as binder-drug adhesion, powder flow, compaction and granulation performances (2)(3)(4)(5). Common methods of characterizing the surface energetics of particulate pharmaceuticals rely on indirect approaches involving the use of characterized or known vapours, liquids or solids as probes as in inverse gas chromatography (IGC) (6), sessile drop contact angle (7) and atomic force microscopy (AFM) (8) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…28) On the other hand, mechanofusion enhanced the surface energy of the lactose carrier. As the surface energy enhancement could be reflected in an increase of the surface adhesiveness, 30,31) there seemed to be discrepancy between the ACI study profile and the measured surface adhesiveness.…”
mentioning
confidence: 97%
“…Elasticity (Davies et al, 2005;Perkins et al, 2009Perkins et al, , 2007 Deformation (local) Hardness (Masterson and Cao, 2008;Perkins et al, 2009) Degradation during storage or processing (Perkins et al, 2009) Force distance measurements Elastic modulus Elasticity (Davies et al, 2005;Perkins et al, 2009, 2007 Hardness (Masterson and Cao, 2008;Perkins et al, 2009) Adhesion Degradation during storage or processing (Perkins et al, 2009) Crystallinity (Perkins et al, 2007) Particle surface energetics (Davies et al, 2005;Perkins et al, 2009) Chemical surface properties (Hooton et al, 2004) Correlation of surface specific properties (Perkins et al, 2007;Ward et al, 2005) Colloidal probe AFM Adhesion Physical interaction between materials (Beach et al, 2002;Hooton et al, 2004;Rogueda et al, 2011) Chemical interaction between materials (Hooton et al, 2004;Islam et al, 2014;Rogueda et al, 2011) Cohesive adhesive balance (Begat et al, 2004a;Jones et al, 2008a,b) Particle surface energetics (Hooton et al, 2006a) Electrostatic surface properties (Götzinger and Peukert, 2003;Kwek et al, 2011) Triboelectric charging (Kwek et al, 2011) Surface polarity (Kwek et al, 2011) Fig. 1.…”
Section: Phase Imagingmentioning
confidence: 99%
“…Similarly, Davies et al (2005) investigated the local elastic modulus of budesonide. Masterson and Cao (2008) and James et al (2008) demonstrated the success of the technique by assessing the elastic moduli of a range of materials: formoterol fumarate, salmeterol xinafoate, salbutamol sulphate, mometasone furoate and salmon calcitonin (Masterson and Cao, 2008) and by evaluating the hardness of drug, lactose and sucrose particles (James et al, 2008).…”
Section: Mechanical Propertiesmentioning
confidence: 99%